ESTRATÉGIAS DE MARKETING APLICADAS A INSTITUIÇÕES DE EDUCAÇÃO SUPERIOR PRIVADAS - Vera Lucia Telles Scaglione (Universidade Federal de Santa Catarina, 2011)
From the beginning of the 21st century, many changes have occurred in the Brazilian cultural scene, especially with regard to the quest for higher education. This is due to increase in the purchasing power of social classes, who seek in higher education both professional growth and personal fulfillment. This phenomenon has generated a growing number of universities in all areas in the country, both public and private. This text provide an analysis of this reality based on literature developed by authors of marketing area, concluding that the private educational institutions need the support of education marketing, that will suggest appropriate strategies to facilitate the capture and maintenance of students in the universities. The students, satisfied with the quality of education offered to them, will act as marketing agents, communicating to the society the qualities of services that were provided by the university.